A bibliography for After Jews and Arabs - Alcalay, Ammiel (Punctum Books, 2021)
"Ammiel Alcalay's groundbreaking work, After Jews and Arabs, published in 1993, redrew the geographic, political, cultural, and emotional map of relations between Jews and Arabs in the Levantine/Mediterranean world over a thousand-year period. Based on over a decade of research and fieldwork in many disciplines--including history and historiography; anthropology, ethnography, and ethnomusicology; political economy and geography; linguistics; philosophy; and the history of science and technology--the book presented a radically different perspective than that presented by received opinion. Given the radical and iconoclastic nature of Alcalay's perspective, After Jews and Arabs met great resistance in attempts to publish it. Though completed and already circulating in 1989, it didn't appear until 1993. In addition, when the book was published, there wasn't enough space to include its original bibliography, a foundational part of the project."